Single calcium channels in native sarcoplasmic reticulum membranes from skeletal muscle. - Suarez-Isla, B A (1986)
Electrical properties of native sarcoplasmic reticulum membranes from rabbit skeletal muscle were investigated using the patch-clamp technique. Bilayers were assembled at the tip of patch pipettes from monolayers formed at the air-water interface of sarcoplasmic reticulum membrane suspensions. The membranes were found to contain a spontaneously active cation channel of small conductance (5 pS in 200 mM CaCl2, symmetrical solutions) that was selective for Ca2+ and Ba2+. Between 50 and 200 mM CaCl2 (symmetrical) the increase in conductance as a function of [Ca2+] fit a hyperbola (K0.5, 83 mM, and gamma max, 7.9 pS) that extrapolated to a single-channel conductance of 0.5 pS at physiological Ca2+ levels. The channel opened in bursts followed by long silent periods of up to a minute. During a burst the channel fluctuated very rapidly with time constants in the millisecond range. The mean burst duration was voltage dependent, increasing from 1.8 s at a pipette voltage of +60 mV to 4.1 s at +80 mV. Over this range, burst frequency decreased with increasing voltage such that the fraction of time spent in the open state (fb) remained constant. Application of 1.6 mM caffeine resulted in activation of the channel that appeared as an increase in mean burst duration. In contrast, 50 microM dantrolene significantly decreased burst frequency, whereas 10 microM nitrendipine had no effect. The functional and pharmacological properties of this Ca2+ channel suggest that it may be important in mediating Ca2+ release from the sarcoplasmic reticulum during excitation-contraction coupling.